Competitive-level differences in yo-yo intermittent recovery and twelve minute run test performance in soccer referees - Castagna, C.; Abt, G.; D'Ottavio, S. (The Journal of Strength and Conditioning Research, 2005)
The aim of this study was to examine yo-yo intermittent recovery test (Yo-Yo test) and 12-minute run test (12MRT) performances in experienced soccer referees of different competitive levels. Three groups (n = 14 each) of experienced Italian soccer referees officiating in the first (series AB, top-level), third (series C, medium-level), and fourth (series D, low-level) division, were randomly submitted to the 12MRT and the Yo-Yo test during 2 testing sessions, 48-hours apart. 12MRT performances were 3,000 ± 112 m; 2,894 ± 99 m; and 2,896 ± 171 m for top-level, medium-level and low-level referees, respectively (p > 0.05). In the Yo-Yo test, the top-level, medium-level, and low-level referees covered 1,874 ± 431 m; 1,360 ± 172 m; and 1,272 ± 215 m, respectively. The test performances of top-level referees in the Yo-Yo test was significantly different from those scored by medium-level and low-level referees (p < 0.05). After the Yo-Yo test, blood lactate concentrations (BLC) were higher in the medium-level and low-level referees compared with the top-level referees (p < 0.05). The results of the present study show that the Yo-Yo test and not the 12MRT can discriminate endurance performance in experienced elite level soccer referees. With respect to its discriminative and match performance validity, the Yo-Yo test may be considered a relevant field test to assess endurance preparedness for experienced soccer referees and a useful tool in talent selection.